2015
DOI: 10.3109/0886022x.2015.1061886
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of polyphenols fromBauhinia hookeriagainst carbon tetrachloride-induced hepato- and nephrotoxicity in mice

Abstract: (2015) Protective role of polyphenols from Bauhiniahookeri against carbon tetrachloride-induced hepato-and nephrotoxicity in mice, Renal Failure, 37:7, 1198Failure, 37:7, -1207 AbstractThe hepatoprotective and nephroprotective activity of a polyphenol-rich fraction (BHPF) obtained from Bauhinia hookeri was investigated against CCl 4 -induced acute hepatorenal toxicity in mice. BHPF was administered (100, 200 and 400 mg/kg/day) for 5 days, then CCl 4 was administered. BHPF pretreatment significantly (p50.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…In ALP assay the blue color developed which was read at 510 nm against blank and the activity is expressed as IU/L of serum. To estimate the TBil readings were taken at 540 nm, the level of total bilirubin was expressed as mg/ dl of serum [9].…”
Section: Biochemical Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…In ALP assay the blue color developed which was read at 510 nm against blank and the activity is expressed as IU/L of serum. To estimate the TBil readings were taken at 540 nm, the level of total bilirubin was expressed as mg/ dl of serum [9].…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…In a number of scientific studies high free radical exposure have been reported to induce membrane lipid peroxidation and protein oxidation as well as deleterious effects on enzymatic system of the cells [6][7][8]. In both of the above mentioned treatments, the serum values of alkaline phosphatase (ALP), aspartate transaminase (AST), alanine transaminase (ALT) and total biliruin (TBil) were found to be abnormally increased, hence are often used as biochemical markers of hepatic injury [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations